Pressurized electro-dewatering of activated sludge: Analysis of electrode configurations (anode). (November 2018) - Yang, Zengjun; Lu, Xuebin; Zhang, Shuting; Zhang, Keqiang; Zhi, Suli; Guo, Haigang; Li, Qian; Yu, Xiaoyan
Graphical abstract: Highlights: The curved surface anodes are applied to pressurized electro-dewatering of sludge. The modified parameters are established for evaluating PED efficiency. The wave plate anode could increase the sludge processing capacity. The use of curved surface anodes improved the gas evacuation from the cell. Abstract: An electric field and mechanical pressure combined are considered an effective electro-dewatering (PED) technology for activated sludge. Here, the curved surface anodes were used for electro-dewatering to improve the effective anode area, and the PED characteristics were investigated for three anode types (flat plate, sawtooth plate and wave plate). First, evaluation methodology of the modified energy consumption ( W ' ED filt ) and the modified processing capacity ( Q ' ED filt a n d Q ' CRO filt ) were established, with electro-dewatering factor ( ξ ED ), to evaluate the PED efficiency of different anode configurations under three raw sludge processing capacity modes. Second, the solid content distribution was analyzed by the layered method, and the electric field and current density distribution were analyzed by the finite element method. Finally, the gas emission mechanism of the curved surface anodes was discussed. When the raw sludge processing capacity and dewatering time (10 min) were the same, nearly the same extent of dewatering was achieved for the wave plate anode as for the flat plate anode. The total filtrate amount was 69.5 g and 59.0 g for the wave plate and flat plate anodes, respectively, and Q ' CRO filt increased by 17.8% for the former. Under the same raw sludge thickness, the dewatering percentages in area A of the sawtooth plate and wave plate anodes were 10% and 11%, respectively, higher than that of the flat plate anode. However, according to numeric simulation results, the current density at the tips of the sawtooth plate anode can reach 740–770 A/m 2, which can reduce its service life as compared to flat plate anode. In area D, gas was more easily emitted from the wave plate anode than from the flat plate anode, reducing the influence of the gas barrier layer on the electrical contact between the sludge cake and the anode.